Highly active absorbent for SO2 removal prepared from coal ash (Part 1). - Nakagawa, K. (Philippine Engineering Journal)
Coal ash samples from Batangas Coal Fired Thermal Powre Plant and limestone from a cement plant in Bulacan were used as raw materials for the preparation of highly active SO2 absorbent. The prepared SO2 absorbents were characterized to determine the effects of mineralogical composition, morphological structure and the type of coal ash used, on SO2 removal efficiency. The desulfurization activity of the SO2 absorbents were determined by varying the curing conditions and CaO content. Among the coal ashes, fly ash exhibited the highest SO2 removal efficiency and longest effective absorption period. The SO2 removal efficiency is closely dependent on the basic conditions during the preparation process of the SO2 absorbent. The SO2 absorption activity increased with the reaction temperature and reached a maximum at 120 degree celcius for fly ash and 130 degree celcius for both bottom ash and slag. Maximum SO2 removal efficiency was also attained by fly ash at 10 hour curing period. Bottom ash and slag had high activity at 15-20 hours of curing time. CaO content in the range of 20-30 percent will give a high SO2 absorption activity.